Seeking Gramsci in the work of Brian Simon - BITTAR, Marisa (Historia y Memoria de la Educación, 2023)
This article examines the results of research on the work and career of Brian Simon (1915-2002), one of the leading historians of English education. It shows the theoretical inspiration for comprehensive school in Soviet psychology and the original way of interpreting Marxism by Brian Simon, that is, anti-determinism, and conviction in education as a factor of change. In addition to the collection in four volumes of Studies in the History of Education, the autobiography, A life in education, and other books by the author, the survey was based on documents and unpublished writings found in the Brian Simon Archive at the Institute of Education/UCL. The conclusions are as follows: 1. The influence of Gramsci could be found in articles and reviews, as well as the courses Professor Simon was involved in from the 1970s onwards; 2. By defending educational reforms that favored the working class, Brian Simon adopted the Marxist view of Gramsci even before knowing the main translation of his work into English (1971); 3. Although a supporter of the Soviet Union, Brian Simon’s reformist protagonism suited Gramsci’s rejection of the Soviet road to socialism since, for him, this was not the appropriate path for “western” countries and for non-revolutionary periods. Finally, the article indicates perspectives of new studies on Marxist intellectuals from different countries whose common interest was Gramsci.